2021
DOI: 10.1029/2020ms002394
|View full text |Cite
|
Sign up to set email alerts
|

Improve the Performance of the Noah‐MP‐Crop Model by Jointly Assimilating Soil Moisture and Vegetation Phenology Data

Abstract: Accurate predictions of water and carbon fluxes in croplands are essential for determining crop yield, hydrologic components, and irrigation schedules and researching climate change (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…These studies also found that the impact of GRACE data assimilation (DA) on snow, runoff, and ET are mixed, partly due to the misrepresentation in model processes 56,57 , requiring either an improvement in model representation of processes that affect the water and energy partitioning 58 or additional constraints for key model states. Here we employ the latter strategy through the joint assimilation of vegetation and surface soil moisture conditions [59][60][61] along with TWS. Assimilating remotely sensed vegetation conditions, such as leaf area index (LAI), and vegetation optical depth has been shown to improve the estimates of terrestrial carbon fluxes, the associated soil moisture, ET, runoff responses, and the representation of extreme events such as wildfires and droughts [62][63][64] .…”
Section: Datasets For Data Assimilationmentioning
confidence: 99%
“…These studies also found that the impact of GRACE data assimilation (DA) on snow, runoff, and ET are mixed, partly due to the misrepresentation in model processes 56,57 , requiring either an improvement in model representation of processes that affect the water and energy partitioning 58 or additional constraints for key model states. Here we employ the latter strategy through the joint assimilation of vegetation and surface soil moisture conditions [59][60][61] along with TWS. Assimilating remotely sensed vegetation conditions, such as leaf area index (LAI), and vegetation optical depth has been shown to improve the estimates of terrestrial carbon fluxes, the associated soil moisture, ET, runoff responses, and the representation of extreme events such as wildfires and droughts [62][63][64] .…”
Section: Datasets For Data Assimilationmentioning
confidence: 99%
“…It should also be noted that a large part of the RMSE is due to bias at most of these stations. Nevertheless, the advantage of SM-DA and LAI-DA on the land surface process variables is well established in prior studies (Albergel et al, 2010;Kolassa et al, 2017;Kumar et al, 2014Lievens et al, 2017;Liu et al, 2011;Xu et al, 2021).…”
Section: Multivariate Da Captures Spatial Signatures Of Flash Drought...mentioning
confidence: 99%
“…Noah-MP can be applied to various spatial scales spanning from point scale locally to ~100-km resolution globally, and temporal scales spanning from sub-daily to decadal time scales. Since its original development, Noah-MP has been used in many important applications, including numerical weather prediction (Suzuki and Zupanski, 2018;Ju et al, 2022), high-resolution climate modeling (Gao et al, 2017;Liu et al, 2017;Rasmussen et al, 2023), land data assimilation (Xu et al, 2021;Nie et al, 2022), drought (Arsenault et al, 2020;Niu et al, 2020;Wu et al, 2021;Abolafia-Rosenzweig et al, 2023a), wildfire (Kumar et al, 2021;Abolafia-Rosenzweig et al, 2022a, 2023b, snowpack evolution (Wrzesien et al, 2015;He et al, 2019;Jiang et al, 2020), hydrology and water resources (Cai et al, 2014;Liang et al, 2019;X. Zhang et al, 2022a;Hazra et al, 2023), crop and agricultural management (Liu et al, 2016;Ingwersen et al, 2018;Warrach-Sagi et al, 2022;Valayamkunnath et al, 2022;Zhang et al, 2020Zhang et al, , 2023, urbanization and heat island (Xu et al, 2018;Salamanca et al, 2018;Patel et al, 2022), biogeochemical cycle (Cai et al, 2016;Brunsell et al, 2021), wind erosion (Jiang et al, 2021), wetland (Z.…”
Section: Introductionmentioning
confidence: 99%